STRATEGI PENINGKATAN KINERJA KARYAWAN MELALUI DIGITAL TRAINING DAN KNOWLEDGE MANAGEMENT - Hatim Syayidah Aslami; Rijatul Anwar (Yayasan Education and Social Center, 2026)
Employee performance improvement has become a strategic agenda for organizations facing digital transformation, changing work patterns, and increasing demands for adaptive capability. Digital training enables organizations to deliver flexible, personalized, measurable, and continuous learning, while knowledge management strengthens the process of identifying, storing, sharing, and applying organizational knowledge. This article aims to examine the strategy for improving employee performance through digital training and knowledge management. The research uses a qualitative literature review method by analyzing concepts, theories, and previous studies related to digital learning, knowledge management, and employee performance. The results of the discussion show that digital training improves employee performance through skill acceleration, learning accessibility, feedback, and work-related competency development. Knowledge management contributes through knowledge sharing, documentation of best practices, organizational memory, and utilization of tacit and explicit knowledge. The integration of digital training and knowledge management creates a continuous learning ecosystem that supports individual capability, work effectiveness, innovation, and organizational productivity. The study recommends that companies develop learning needs analysis, digital learning platforms, knowledge repositories, communities of practice, mentoring systems, performance-based evaluation, and leadership support to optimize employee performance.